Determinants of Foreign Direct Investment in Fast-Growing Economies: A Study of BRICS and MINT - Akpan Uduak; Isihak Salisu; Simplice A. Asongu (African Governance and Development Institute (AGDI), 2014)
This study employs panel analysis to examine the determinants of foreign direct investment (FDI) in Brazil, Russia, India, China, and South Africa (BRICS) and Mexico, Indonesia, Nigeria, and Turkey (MINT) using data for eleven years i.e. 2001 2011. First, it uses pooled time-series cross sectional analysis to estimate the model on determinants of FDI for three samples: BRICS only, MINT only, and BRICS and MINT combined; then, random effects model is also employed to estimate the model for BRICS and MINT combined. The results show that market size, infrastructure availability, and trade openness play the most significant roles in attracting FDI to BRICS and MINT while the roles of availability of natural resources and institutional quality are insignificant. Given that FDI inflow to a country has the potential of being mutually beneficial to the investing entity and host government, the challenge is on how BRICS and MINT can sustain the level of FDI inflow and ensure it results in economic growth and socio-economic transformation. To sustain the level of FDI inflow, governments of BRICS and MINT need to ensure that their countries remain attractive for investment. BRICS and MINT also need to ensure that their economies absorb substantial skills and technology spillovers from FDI inflow to promote sustainable long-term economic growth by investing more in their human capital. The study is significant because it contributes to literature on determinants of FDI by extending the scope of previous studies which often focus only on BRICS.
Keywords: 330; FDI; determinants; fast-growing economies; BRICS; MINT